The impact of pre-rehydration guided by carotid corrected flow time on hypotension prevention following general anesthesia induction in patients undergoing gastrointestinal surgery: a prospective randomized controlled trial - Li, Min; Li, Feng; Yu, Jiali; Tang, Xixi; Zhou, Chengfu; Chen, Qi; Liu, Hongliang (Frontiers in Medicine, 2024)
Background: Patients undergoing gastrointestinal surgery often experience hypotension following general anesthesia induction due to insufficient volume. This study aimed to assess whether prerehydration guided by carotid corrected flow time (FTc) could mitigate post-induction hypotension induced by general anesthesia. Methods: Patients undergoing resection of gastrointestinal tumors were assigned to either the conventional treatment group (Group C) or the fluid treatment group based on FTc (Group F). Within Group F, patients were further divided into Group A (Carotid FTc < 340.7 ms) and Group B (Carotid FTc ≥ 340.7 ms) based on pre-rehydration carotid FTc values. Group A patients received pre-rehydration with 250ml of colloids (hydroxyethyl starch -HES) administered within 15 minutes until Carotid FTc reached ≥ 340.7 ms to counteract hypovolemia prior to induction. Patients in Group B and Group C received a continuous HES infusion at a rate of 6 ml/kg/h 30 minutes before induction to compensate for physiological fluid loss. All patients received a perioperative background infusion of 3 ml/kg/h compound sodium chloride, with infusion rates optimized based on mean arterial pressure (MAP) and heart rate (HR). The incidence of postinduction hypotension was compared between Group C and Group F, as well as between Group A and Group B. Results: The incidence of hypotension after induction was significantly lower in Group F compared to Group C (26.4% vs. 46.7%, respectively; P < 0.001). Patients in Group A received significantly more pre-rehydration, leading to a greater increase in Carotid FTc values compared to Group B (336.5 ± 64.5 vs. 174.3 ± 34.1, P = 0.002). However, no significant difference in Carotid FTc values after pre-rehydration was observed between the groups. There was no significant difference in the incidence of hypotension after general anesthesia induction between Group A and Group B (22.9% vs. 28.8%, P = 0.535). Conclusions: Pre-rehydration based on FTc can effectively reduce the occurrence of post-induction hypotension in patients undergoing gastrointestinal surgery who present with insufficient volume.